2014
DOI: 10.1044/1092-4388(2013/12-0352)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spaced Retrieval Training on Semantic Memory in Alzheimer's Disease: A Systematic Review

Abstract: The findings indicate that SRT is an effective semantic memory training technique for people with AD, and consequently, recommendations are suggested for implementing SRT in practice settings. Continued research in this domain is also warranted to address limitations and gaps in the current body of research evidence, including variability in SRT protocols, effects of dementia severity on learning outcomes, maintenance effects, generalization, and the role of explicit and implicit learning in SRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Another systematic review reported that the effect sizes of memory strategy trainings ranged from –1.18 to 0.88 in individuals with MCI [35]. Although there have been no clinical trials to investigate the effect size of SRT in patients with MCI, a meta-analysis of the effects of SRT on semantic memory in patients with mild AD reported that the effect sizes varied substantially from 0.67 to 37.97 across studies [10]. The authors attributed the wide variation in the effect size of SRT between studies to differences in protocols for SRT, sizes of study samples, outcome measures, and quality of the clinical trials [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review reported that the effect sizes of memory strategy trainings ranged from –1.18 to 0.88 in individuals with MCI [35]. Although there have been no clinical trials to investigate the effect size of SRT in patients with MCI, a meta-analysis of the effects of SRT on semantic memory in patients with mild AD reported that the effect sizes varied substantially from 0.67 to 37.97 across studies [10]. The authors attributed the wide variation in the effect size of SRT between studies to differences in protocols for SRT, sizes of study samples, outcome measures, and quality of the clinical trials [10].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, SRT was found to improve prospective memory [8] and the capacity to learn face–name associations [9] in patients with MCI. SRT also improves semantic memory and behavioral strategies in patients with dementia [10, 11]. Studies have speculated that SRT improves learning through a combination of ecologically valid priming, spacing effect, conditioning, and errorless learning [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made in the field of successful training or coaching interventions for people with dementia, for example: Errorless Learning (EL), Errorful Learning (EF), Space Retrieval Training (SRT), and Method of Vanishing Cues (MVC) (Clare, 2008). However, the findings of previous reviews on cognitive interventions for people with dementia (Clare and Jones, 2008;Hopper et al, 2013;Oren et al, 2014) provide insufficient information to determine what training or coaching intervention(s) is/are most effective for people with dementia to learn how to use the tablet and its applications. Most reviews concentrate on cognitive stimulation in general which aims to improve cognition, behavior and quality of life, and on cognitive training which aims to improve the performance on specific cognitive tasks (Clare, 2008).…”
Section: Methods Of Preclinical or Theoretical Phase (Phase 0)mentioning
confidence: 99%
“…The participant may continue to look at the target photograph and repeat the name, or view the re-arrangement of the array in between trials. Oren, Willerton, and Small (2014) also conducted a review of SR, and provide additional points to consider. Along with issues of procedural clarity, no measures of treatment integrity or interobserver agreement have been reported in the literature.…”
Section: Spaced Retrievalmentioning
confidence: 99%